Study the Local Scour around different Shapes of Non-Uniform Piers - Ahmed, Saja I.; Khassaf, Saleh I. (Basrah Journal for Engineering Sciences, 2020)
Scour around bridge foundations is one of the major causes of severe damage to bridge structures. This study experimentally investigated the effects of key parameters, including pier shape, foundation shape, foundation level, flow intensity, and Froude number, on local scour for non-uniform pier geometries. Three foundation shapes (rectangular, oblong, and hexagonal) and three pier shapes (rectangular, oblong, and hexagonal) were examined, with a constant foundation depth of 8 cm. The results demonstrated that scour depth is strongly influenced by foundation level and by the shapes of both piers and foundations. Among the tested configurations, the hexagonal foundation exhibited the lowest scour depth, followed by oblong and rectangular shapes, respectively. Positioning the foundation below the bed level further reduced scour depth around the pier. Additionally, the hexagonal pier produced the minimum scour because of its smaller exposed surface area. These findings highlight the importance of structural geometry and foundation placement in minimizing local scour at bridge piers.